Rancang Bangun Sistem Informasi Cyber Campus Karyawan pada Stikom Surabaya - Presditya, Moninda Bagus; Sudarmaningtyas, Pantjawati; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Stikom Surabaya has a Cyber Campus Information System (Sicyca) intended for students and employees. Users employee for itself consists of educators and education personnel. One of the critical success factor in the implementation of a system that is when the systems were well received by users. Based on the results of the initial questionnaire intended for users Sicyca employees filled out by 23 educators and 23 education personnel, There are as many as 58.70% of respondents still not happy with the display interfaces now, 54.35% of respondents said time loading time over 10 second and 56.52% of respondents of the total educators are still not satisfied in terms of functionality. It is necessary to repair with some development on the web Sicyca especially in the use of web programming language which was originally still using ASP, will be developed using PHP. This application also provides information on the development of employee performance that is displayed in the dashboard.